A Digital Method to Fabricate the Ocular Portion of An Orbital Prosthesis with A Smartphone Camera, Color Calibration and Digital Printing. Issue 1 (17th December 2020) - Jauregui Ulloa, Jaccare; Salazar‐Gamarra, Rodrigo; Mesquita, Alfredo Mikail M.; Aguirre, Felipe; Dib, Luciano Lauria
Abstract: Conventional techniques described in the literature for the manufacture of ocular prostheses are time‐consuming since they involve manual work. The use of technologies could improve this laborious process, providing better esthetic outcomes. This technique describes how to manufacture the ocular portion of an orbital prosthesis using a smartphone camera, color calibration with a tooth shade guide, and digital printing. This method allows clinicians to fabricate customized ocular prosthesis by using a photograph of the patient's eye, thus eliminating the need for hand‐painting and manual work, and reducing fabrication time.